Engineering functional microvessels in synthetic polyurethane random-pore scaffolds by harnessing perfusion flow. (October 2020) - Wright, Meghan EE.; Yu, Jonathan K.; Jain, Devika; Maeda, Azusa; Yeh, Shu-Chi A.; DaCosta, Ralph S.; Lin, Charles P.; Santerre, J. Paul
Abstract: Recently reported biomaterial-based approaches toward prevascularizing tissue constructs rely on biologically or structurally complex scaffolds that are complicated to manufacture and sterilize, and challenging to customize for clinical applications. In the current work, a prevascularization method for soft tissue engineering that uses a non-patterned and non-biological scaffold is proposed. Human fibroblasts and HUVECs were seeded on an ionomeric polyurethane-based hydrogel and cultured for 14 days under medium perfusion. A flow rate of 0.05 mL/min resulted in a greater lumen density in the constructs relative to 0.005 and 0.5 mL/min, indicating the critical importance of flow magnitude in establishing microvessels. Constructs generated at 0.05 mL/min perfusion flow were implanted in a mouse subcutaneous model and intravital imaging was used to characterize host blood perfusion through the construct after 2 weeks. Engineered microvessels were functional (i.e. perfused with host blood and non-leaky) and neovascularization of the construct by host vessels was enhanced relative to non-prevascularized constructs. We report on the first strategy toward engineering functional microvessels in a tissue construct using non-bioactive, non-patterned synthetic polyurethane materials.